The Analysis of Household Car and Motorcycle Ownerships Using Poisson Regression (Case Study: Denpasar-Bali) - D. M. Priyantha Wedagama Wedagama (Institut Teknologi Bandung, 2009)
Abstract. This study examines household factors which influence car and motorcycle ownerships in the city of Denpasar, Bali using a Poisson regression model. The study found that the increase in number of workers and students in a household may affect the probability of owning motorcycle by the household. Meanwhile, the increase in number of family member and total travel distance may affect household preference to own a car. In addition, car capacity and other factors may increase household preference to own a car. None of these variables, however, significantly influenced on both car and motorcycle ownerships. In other words, the household had a separate preference when purchasing either a car or a motorcycle. The sensitivity analyses show a-50% increase in number of workers and students may increase motorcycle ownership by 1 unit and a-50% increase in total travel distance by all household members may increase car ownership by 1 unit. Abstrak. Pada studi ini digunakan regresi Poisson untuk menyelidiki faktor-faktor lokal rumah tangga yang dapat mempengaruhi kepemilikan mobil dan sepeda motor di kota Denpasar, Bali. Dari studi ini disimpulkan bahwa pertambahan jumlah pekerja dan pelajar/mahasiswa dalam satu rumah tangga secara signifikan dapat meningkatkan peluang kepemilikan sepeda motor. Sementara itu kepemilikan mobil secara signifikan dapat dipengaruhi oleh jumlah anggota keluarga, total jarak tempuh perjalanan oleh semua anggota keluarga, dan kapasitas mobil. Akan tetapi tidak ada faktor-faktor lokal rumah tangga yang berpengaruh sekaligus pada kepemilikan mobil dan sepeda motor. Dengan perkataan lain, satu rumah tangga mempunyai preferensi masing-masing di dalam keputusan untuk membeli sepeda motor atau mobil. Analisis sensitifitas memperlihatkan bahwa pertambahan sebesar 50% dari jumlah pekerja dan pelajar/mahasiswa dalam satu rumah tangga dapat meningkatkan kepemilikan sepeda motor sebesar satu unit dan peningkatan sebesar 50% total jarak tempuh perjalanan oleh semua anggota keluarga dapat meningkatkan kepemilikan mobil juga sebesar satu unit.